TREATMENT OF PEYRONIE’S DISEASE - Кызласов, Павел Сергеевич; Мартов, Алексей Георгиевич; Помешкин, Евгений Владимирович; Трояков, Владислав Маратович; Капсаргин, Федор Петрович (Medicine in Kuzbass, 2017)
Here we present a review of global data on known methods of treatment of Peyronie’s disease. A comparative analysis of surgical techniques is performed. The analysis revealed that there is no an «ideal» method of surgical management for Peyronie’s disease. We came to the conclusion that this issue needs further research.